2010
DOI: 10.1007/s12098-009-0336-2
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged neonatal interhospital transport on road: Relevance for developing countries

Abstract: Long distance neonatal transport on road is feasible and with a qualified team results can be comparable to those transported from shorter distances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 16 publications
2
14
1
Order By: Relevance
“…18 However, Kumar et al found that longdistance neonatal transport on road is feasible, and with a qualified team, results can be comparable to those transported from shorter distances. 19 In the present study, long-distance land-based neonatal transport increased the adverse effects of TTN in newborns. Patients from outside the city were admitted to the NICU later than patients from inside the city.…”
Section: Discussionsupporting
confidence: 45%
“…18 However, Kumar et al found that longdistance neonatal transport on road is feasible, and with a qualified team, results can be comparable to those transported from shorter distances. 19 In the present study, long-distance land-based neonatal transport increased the adverse effects of TTN in newborns. Patients from outside the city were admitted to the NICU later than patients from inside the city.…”
Section: Discussionsupporting
confidence: 45%
“…Lack of appropriate transport systems puts these neonates at risk of poor outcome even when they are eventually admitted to hospital [28][29][30]48]. One way to address this is to shorten travel time by improving the quality of transport to minimise the effect of distance as studies have shown that neonates can be transferred safely across long distances by road [10,51]. Alternatively, distance to the closest facility can be reduced by increasing the number of admission facilities and bringing specialized care closer to communities [13].…”
Section: Discussionmentioning
confidence: 99%
“…It is of utmost importance to understand that patient stabilization is an essential requirement for adequate transport, regardless of transport time or distance. 20 The transport team must confirm patient stability before starting the transport, so that its benefits outweigh the inherent risks. 1 For the transport to be successful, with minimal risks, the patient must be well-monitored patient, undergoing assisted mechanical ventilation, if necessary, after receiving medications at the local hospital before transpor.…”
Section: Discussionmentioning
confidence: 99%
“…Axillary temperature is one of the variables that change the most during transport, as shown in studies that used it as a transport assessment parameter. 12,20,22 If the teams were trained specifically in neonatal transport, the results would probably be even better. The authors suggest an integration between SAMU, MOH, and SBP in order to systematically train healthcare staff in neonatal transport, reassessing neonatal transport service teams and exchanging previous experience on patient transport and care of the transported newborn.…”
Section: Discussionmentioning
confidence: 99%